RELATIONS OF THE MORPHOLOGICAL CHARACTERISTICS AND MOTOR ABILITIES WITH JUMP FOWRARD AND TRIPLE JUMP OF STUDENTS AT THE FACULTY OF SCIENCE AND SPORT - Rashiti Naser; Ajvazi Vlora; Adem Nura; Fadil Nika (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
In order to examine the impact of anthropometrical characteristics and motor skills during the tests' implementation of the jump forward and triple jump from place, the experimental research was carried out on a sample of 100 second year students from the Faculty of Physical Education and Sport in Prishtine. For the purposes of this study were measured eight anthropometrical characteristics and ten tests for assessing motor skills, which made the predictor system of variables. To assess the explosive force of the type of jumpiness, applied were tests long jump forward and triple jump from place. Data was processed with the basic descriptive statistical parameters and regression analysis. Based on the results of this research and the discussion ,can be concluded that the applied system of predictor motor tests, have significant influence on the manifestation of the explosive force of students at the Faculty of Physical Education and Sport in Prishtine, i.e., it is possible to predict (forecast) the results of tests for explosive power based on the predictor system of respondents